The Study of the Late Mediaeval Temple Architectures of Tripura (The North Eastern State of India)- A Style Evolved Due to the Multi-Cultural Assimilation During the Manikya Period (Journal of Advanced Research in Social Sciences, 2020)
The purpose of this study is to show the assimilated styles, motifs and designs of the Late Mediaeval Temple Architectures of Tripura. Like the other parts of India, Tripura has been an important centre of interaction of several cultures and traditions. The state is a home to numerous Tribes having different traditions and cultures. Therefore there is a wide variety in the life style and cultures of this state. Due to the friendly nature of the Manikya kings, the state was globally well connected. In the Royal courtyard, many scholars, artists, architects and other literates were invited for cultural exchanges at that time. We can see the influences of those sharing thoughts in the Architectures of this state. The temples constructed during the late 15th-16th century exhibits motifs influenced from the Indo-Islamic architectures, Bengal temples, Indo- Burmese style and other indigenous elements of this region. These temples reflect a synthesis of the arts, ideas, religious beliefs, values and the way of life during the Manikya ages.